How important is the eggshell as a source for initial acquisition of Salmonella in hatchling turtles?. Issue 2 (28th January 2016) - Holgersson, Mikael C.N.; Nichols, Wade A.; Paitz, Ryan T.; Bowden, Rachel M.
ABSTRACT: How and when turtles first acquire gut microflora is largely speculative. In this study, the eggshell and hatching process were evaluated for their role in the initial acquisition of Salmonella, by red‐eared slider turtles ( Trachemys scripta elegans ). First, we examined whether the eggshell is a viable substrate for bacterial persistence during incubation, and if internal egg components (i.e., albumen, yolk, and embryo) have detectable bacterial loads. Second, we experimentally manipulated Salmonella by treating eggs with combinations of Salmonella and gentamicin, an effective Gram‐negative antibiotic. We found that the eggshell is a viable substrate for maintaining bacteria, as well as an effective barrier to Salmonella transmission as internal egg components were largely bacteria‐free. Water samples collected 18 days post‐hatch from individuals that were experimentally inoculated with a topical application of Salmonella as eggs had a higher prevalence of Salmonella than those from eggs inoculated with Salmonella but topically treated with gentamicin prior to hatching, control eggs, and eggs only treated with gentamicin, but by day 35 post‐hatch there were no detectable differences among the treatment groups. Though it can also act as a barrier that prevents the bacteria from infecting the embryo prior to hatching these findings suggest that the eggshell is a likely source of Salmonella infection in turtle hatchlings. J. Exp. Zool. 9999A:XX–XX, 2016. © 2016 Wiley Periodicals, Inc.